KESADARAN WAJIB PAJAK, KEWAJIBAN MORAL, DAN AKUNTABILITAS PELAYANAN PUBLIK PADA KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR - Nadya Fitri Ramadhany; Adelina Suryati (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
The aim of this research is to examine and experimentally evaluate the influence of taxpayer knowledge, moral obligation, and accountability in public service on auto taxpayer compliance. The study was conducted at Cikarang Samsat. Primary data from 98 survey participants and processable data from all 98 surveys were utilized. A convenience sampling approach was employed, and the data analysis method used was multiple linear regression. The findings of this study indicate that moral obligation and public responsibility variables do not have an impact on auto taxpayer compliance. However, in Cikarang Samsat, the variable of taxpayer knowledge does influence each taxpayer's compliance with regulations.